2012
DOI: 10.3727/194982412x13462021398010
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fused Circulations to Investigate the Role of Apolipoprotein E as Amyloid Catalyst and Peripheral Sink in Alzheimer's Disease

Abstract: Apolipoprotein E (apoE) synthesized in liver and brain plays a key role in both cholesterol transport and Alzheimer's disease (AD): apoE-knockout mice develop hypercholesterolemia and atherosclerosis and cannot support AD amyloid deposition. The ApoE4 allele is the strongest genetic risk factor for late-onset AD, and apoE4 protein preferentially catalyzes amyloid-beta (Aβ) peptide fibrillization in vitro and amyloid plaque deposition in vivo. Circulating apoE may also have the potential to draw Aβ from the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(52 reference statements)
1
10
0
Order By: Relevance
“…ΔR ct values due to the nonspecific binding were negligible compared to ΔR ct detected upon the binding between Aβ and ApoE on the surface. This result was in parallel with the reported strong affinity between ApoE isoforms and Aβ peptides …”
Section: Resultssupporting
confidence: 88%
“…ΔR ct values due to the nonspecific binding were negligible compared to ΔR ct detected upon the binding between Aβ and ApoE on the surface. This result was in parallel with the reported strong affinity between ApoE isoforms and Aβ peptides …”
Section: Resultssupporting
confidence: 88%
“…It is unlikely that changes in Aβ production, degradation, or transport across BBB play dominant roles in the reduction of brain Aβ of the parabiotic AD mice, as there were no significant changes in the expression of APPfl, CTF-α, CTF-β, BACE1, IDE, NEP, LRP-1, and RAGE. A recent study shows that parabiosis between APPswe/PS1 mouse with ApoE gene and APPswe/PS1 mouse without ApoE gene did not reduce compact plaque burden in the brain of APPswe/PS1 mice with the ApoE gene [ 31 ]; suggesting that the systematic inflammation or immune responses induced by the parabiosis surgery would not be responsible for the large reduction of brain Aβ burden observed in the present study. In addition, both acute and chronic systematic inflammation are suggested to accelerate but not halt Aβ deposition and disease progress of AD [ 13 , 14 , 19 ].…”
Section: Discussionmentioning
confidence: 52%
“…The age-matched female Wt ( n = 8) and Tg mice ( n = 8) without parabiosis were used in parallel as controls. The parabiosis was performed following procedures as previously described [ 31 ]. Briefly, animals were anesthetized with ketamine (100 mg/kg), xylazine (20 mg/kg), and acepromazine (3 mg/kg), and placed in a parallel orientation.…”
Section: Methodsmentioning
confidence: 99%
“…We also introduced apoE itself into the circulation via parabiosis and found that it induced amyloid clearance without entering the brain in AD model mice [38]. Thus the “Peripheral Sink Hypothesis” became a viable alternative or addition to the Amyloid Cascade Hypothesis, with apoE potentially playing an additional role as an A β -binding peripheral protein.…”
Section: Background: Apoe In Aβ/amyloid Clearancementioning
confidence: 99%